2022
DOI: 10.5552/crojfe.2022.1054
|View full text |Cite
|
Sign up to set email alerts
|

Use of Impact Penetrometer to Determine Changes in Soil Compactness After Entracon Sioux EH30 Timber Harvesting

Abstract: Wood harvesting with the use of wheeled harvesters is now common in Polish and Czech forests. While moving in the forest, the wheels of these machines affect the forest soil and the extent of this impact is interesting. The paper presents the results of measurements of the changes that occur in the soil on the operational trails after the timber harvesting using the Entracon Sioux EH30 thinning harvester. The measurements were taken on fragments of three operational trails, in and between the ruts and at a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In our case, a weak relationship was observed between the longitudinal slope and BD in the ruts. Kormanek and Dvořák [38] concluded that machine traffic contributed to the slight lowering of MC in the ruts in relation to the control. In our case, the highest MC values were recorded in the ruts of the technological trails.…”
Section: Bulk Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, a weak relationship was observed between the longitudinal slope and BD in the ruts. Kormanek and Dvořák [38] concluded that machine traffic contributed to the slight lowering of MC in the ruts in relation to the control. In our case, the highest MC values were recorded in the ruts of the technological trails.…”
Section: Bulk Densitymentioning
confidence: 99%
“…Picchio et al [37] reported that PR in undisturbed areas was significantly lower than in soils disturbed by machine traffic in their study focused on Hyrcanian and Camaldoli forests managed in a close-to-nature system and with skidder extraction. Kormanek and Dvořák [38] stated that PR was higher in the ruts compared to measurements next to and between the ruts when a tracked Entracon Sioux EH30 was used. Kruskal-Wallis tests showed similar results for the differences between PR in particular measurement locations in our case as well.…”
Section: Penetration Resistancementioning
confidence: 99%
“…When permeability is low, either from natural impervious layers, compacted soils, or human-made factors, the outflow speed diminishes, potentially causing ponding or surface runoff. Such situations occur with intensive use in agricultural areas [22] and forest areas [23][24][25][26]. In container production, where the container and a minimal amount of substrate are elevated from the ground, water outflows freely.…”
Section: Discussionmentioning
confidence: 99%
“…Over 13,920,000 m 3 of merchantable timber are harvested in thinned stands, including the majority of medium-sized assortments important for the timber sector (Statistical Yearbook of Forestry 2020). Mechanized logging with harvesters and forwarders, has its particular justification in thinning stands, primarily due to its ecological, economic and ergonomic advantages (Sowa et al 2007, Dvořák et al 2011, Zinkevičiuset al 2012, Kulak et al 2017, Kováč et al 2021, Mederski et al 2018, Szewczyk et al 2020, Kormanek & Dvořák 2022.…”
Section: Introductionmentioning
confidence: 99%